2024
DOI: 10.1001/jamapediatrics.2023.4907
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nativity and Preterm Birth

Xiaoning Huang,
Kristen Lee,
Michael C. Wang
et al.

Abstract: ImportancePreterm birth is a major contributor to neonatal morbidity and mortality, and considerable differences exist in rates of preterm birth among maternal racial and ethnic groups. Emerging evidence suggests pregnant individuals born outside the US have fewer obstetric complications than those born in the US, but the intersection of maternal nativity with race and ethnicity for preterm birth is not well studied.ObjectiveTo determine if there is an association between maternal nativity and preterm birth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies on the health of African-born immigrants in the United States have found a lower risk of several health outcomes compared with their United States-born counterparts, including diabetes, risk factors for cardiovascular disease, cancer mortality, and adverse perinatal outcomes. 6–14 For instance, African-born Black women have lower risks of preterm birth, small for gestational age birth (SGA), and low birthweight, compared with United States-born Black women. 9,10,12…”
mentioning
confidence: 99%
“…Previous studies on the health of African-born immigrants in the United States have found a lower risk of several health outcomes compared with their United States-born counterparts, including diabetes, risk factors for cardiovascular disease, cancer mortality, and adverse perinatal outcomes. 6–14 For instance, African-born Black women have lower risks of preterm birth, small for gestational age birth (SGA), and low birthweight, compared with United States-born Black women. 9,10,12…”
mentioning
confidence: 99%